An access control framework for mobile applications - Abdunabi, Ramadan, author; Ray, Indrakshi, advisor; France, Robert, committee member; Ray, Indrajit, committee member; Turk, Daniel, committee member (Colorado State University. Libraries, 2013)
With the advent of wireless and mobile devices, many new applications are being developed that make use of the spatio-temporal information of a user in order to provide better functionality. Such applications also necessitate sophisticated authorization models where access to a resource depends on the credentials of the user and also on the location and time of access. Consequently, traditional access control models, such as, Role-Based Access Control (RBAC), has been augmented to provide spatio-temporal access control. However, the velocity of technological development imposes sophisticated constraints that might not be possible to support with earlier works. In this dissertation, we provide an access control framework that allows one to specify, verify, and enforce spatio-temporal policies of mobile applications. Our specification of spatio-temporal access control improves the expressiveness upon earlier works by providing features that are useful for mobile applications. Thus, an application using our model can specify different types of spatio-temporal constraints. It defines a number of novel concepts that allow ease of integration of access control policies with applications and make policy models more amenable to analysis. Our access control models are presented using both theoretical and practical methods. Our models have numerous features that may interact to produce conflicts. Towards this end, we also develop automated analysis approaches for conflict detection and correction at model and application levels. These approaches rigorously check policy models and provide feedback when some properties do not hold. For strict temporal behaviour, our analysis can be used to perform a quantitative verification of the temporal properties while considering mobility. We also provide a number of techniques to reduce the state-space explosion problem that is inherent in model checkers. Furthermore, we introduce a policy enforcement mechanism illustrates the practical viability of our models and discusses potential challenges with possible solutions. Specifically, we propose an event-based architecture for enforcing spatio-temporal access control and demonstrate its feasibility by developing a prototype. We also provide a number of protocols for granting and revoking access and formally analyze these protocols in order to provide assurance that our proposed architecture is indeed secure.
Keywords: access control; access control protocol; computer security; enforcement; policy model; RBAC